2018
DOI: 10.3168/jds.2018-14748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary cation-anion difference on acid-base status and dry matter intake in dry pregnant cows

Abstract: The objective was to determine if the reduction in dry matter (DM) intake of acidogenic diets is mediated by inclusion of acidogenic products, content of salts containing Cl, or changes in acid-base status. The hypothesis was that a decrease in intake is mediated by metabolic acidosis. Ten primigravid Holstein cows at 148 ± 8 d of gestation were used in a duplicated 5 × 5 Latin square design. The dietary cation-anion difference (DCAD) of diets and acid-base status of cows were manipulated by incorporating an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 37 publications
(56 reference statements)
7
40
0
2
Order By: Relevance
“…It is possible, therefore, that the difference in BW may reflect less rumen fill associated with less DMI as well as, or independent of, an effect on body tissue mass. An effect of a diet with negative DCAD is to depress DMI, as demonstrated by Charbonneau et al (2006), Santos et al (2019), and Zimpel et al (2018), which was also observed in the current study. As anticipated, urinary pH reduced by 1.226 U in the treated cows, reflecting the metabolic acidification resulting from the strong ion differences of the treatments.…”
Section: Discussionsupporting
confidence: 88%
“…It is possible, therefore, that the difference in BW may reflect less rumen fill associated with less DMI as well as, or independent of, an effect on body tissue mass. An effect of a diet with negative DCAD is to depress DMI, as demonstrated by Charbonneau et al (2006), Santos et al (2019), and Zimpel et al (2018), which was also observed in the current study. As anticipated, urinary pH reduced by 1.226 U in the treated cows, reflecting the metabolic acidification resulting from the strong ion differences of the treatments.…”
Section: Discussionsupporting
confidence: 88%
“…Luebbe et al [44] also reported that urinary pH increased as DCAD increased. These decrease in pH of urine noticed during the feeding period when fed total mix ration with a DCAD between −100 and −200 mEq/kg of DM [45,35,9]. Our findings reflect that increase or decrease in urine pH in DCAD fed animals was because of the alkaline or acidic nature of the diet respectively, which is the function of salts used for the respective mineral composition.…”
Section: Effect On Urine Phsupporting
confidence: 53%
“…The current study showed that reducing the DCAD caused a reduction in DMI prepartum, but the same reduction in DCAD improved intake postpartum. The decline in intake prepartum seems to be induced by the metabolic acidosis and not by use of a particular source of strong ions supplemented to the diet (Vagnoni and Oetzel, 1998;Zimpel et al, 2018). Zimpel et al (2018) recently showed that feeding a diet with negative DCAD induced a compensated metabolic acidosis and depressed DMI, but the same diet with acidogenic product supplemented with salts containing strong cations to result in a positive DCAD prevented the depression in intake.…”
Section: Discussionmentioning
confidence: 99%